Status and distribution of Phytophthora leaf blight and fruit rot of capsicum in Himachal Pradesh and its management through fungicides - and D.K. BANYAL, JAYA CHAUDHARY* (Indian Phytopathology, 2013)
Leaf blight and fruit rot of capsicum caused by Phytophthora nicotianae var. nicotianae is one of the most destructive diseases occurring widely in different parts of the world. The disease causes huge losses to this crop particularly during rainy season. In Himachal Pradesh, 37 locations were surveyed during cropping season in 5 districts and disease was recorded at all the locations and disease incidence varied from 12.5 to 72.7 per cent whereas, severity ranged between 11.3 to 55.4 per cent. Maximum disease was recorded in Mandi and Kullu districts. In vitro evaluation of fungicides showed that Ridomil-MZ and Moximate @ 2000 Î¼g/ml were highly fungitoxic as compared to other fungicides. Similarly under field conditions foliar applications of Ridomil-MZ @ 0.25 per cent were highly effective giving 70.1 per cent control of leaf blight and 84.9 per cent control of fruit rot with 160.9 per cent increase in yield over check. Moximate @ 0.25 per cent was also found effective with 57.6 per cent control of leaf blight and 67.5 per cent fruit rot control with 100 per cent increase in yield over check.